Light-dependent changes in the outer plexiform layer of the mouse retina - Haley, Tammie L.; Hecht, Ryan M.; Ren, Gaoying; Carroll, James R.; Aicher, Sue A.; Duvoisin, Robert M.; Morgans, Catherine W. (Frontiers in Ophthalmology, 2023)
The ability of the visual system to relay meaningful information over a wide range of lighting conditions is critical to functional vision, and relies on mechanisms of adaptation within the retina that adjust sensitivity and gain as ambient light changes. Photoreceptor synapses represent the first stage of image processing in the visual system, thus activity-driven changes at this site are a potentially powerful, yet under-studied means of adaptation. To gain insight into these mechanisms, the abundance and distribution of key synaptic proteins involved in photoreceptor to ON-bipolar cell transmission were compared between light-adapted mice and mice subjected to prolonged dark exposure (72 hours), by immunofluorescence confocal microscopy and immunoblotting. We also tested the effects on protein abundance and distribution of 0.5-4 hours of light exposure following prolonged darkness. Proteins examined included the synaptic ribbon protein, ribeye, and components of the ON-bipolar cell signal transduction pathway (mGluR6, TRPM1, RGS11, GPR179, Goα). The results indicate a reduction in immunoreactivity for ribeye, TRPM1, mGluR6, and RGS11 following prolonged dark exposure compared to the light-adapted state, but a rapid restoration of the light-adapted pattern upon light exposure. Electron microscopy revealed similar ultrastructure of light-adapted and dark-adapted photoreceptor terminals, with the exception of electron dense vesicles in dark-adapted but not light-adapted ON-bipolar cell dendrites. To assess synaptic transmission from photoreceptors to ON-bipolar cells, we recorded electroretinograms after different dark exposure times (2, 16, 24, 48, 72 hours) and measured the b-wave to a-wave ratios. Consistent with the reduction in synaptic proteins, the b/a ratios were smaller following prolonged dark exposure (48-72 hours) compared to 16 hours dark exposure (13-21%, depending on flash intensity). Overall, the results provide evidence of light/dark-dependent plasticity in photoreceptor synapses at the biochemical, morphological, and physiological levels.